Transformation Of Narcotics Evidence Supervision At Banjarbaru Police Resort, South Kalimantan Regional Police In Realizing Accountability And Public Trust - Prayuda Bima Wibawa; Elvianus Laoli; Novi Indah Earlyanti; Oscarius Yudhi Pratama (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study discusses the transformation of the supervision system of narcotics evidence at the Banjarbaru Police Resort as an effort to enhance accountability in evidence management and to build public trust in the police institution. The focus of this research is to analyze how the transformation of narcotics evidence supervision is implemented at the Banjarbaru Police Resort, to identify the obstacles encountered, and to evaluate its impact on improving accountability and public trust.         This study employs public trust theory and POAC (Planning, Organizing, Actuating, Controlling) theory, as well as the concept of internal supervision as the analytical framework. The research method used is a qualitative approach with primary data obtained through in-depth interviews and field observations, and secondary data derived from official documents, laws and regulations, literature, and related reports. Data collection techniques include observation, interviews, documentation, and data triangulation to ensure data validity. Data analysis is conducted through data reduction, data presentation, and conclusion drawing and verification.         The results and discussion indicate that the transformation of narcotics evidence supervision at the Banjarbaru Police Resort has been carried out through the implementation of stricter standard operating procedures (SOP), the use of digital-based administrative systems, enhanced layered supervision by direct supervisors, and the strengthening of internal supervisory functions. However, in practice, there are still several obstacles such as limitations in facilities and infrastructure, suboptimal integration of digital systems, and uneven human resource capacity in understanding and complying with procedures. This transformation has gradually improved transparency and accountability in evidence management, thereby positively impacting the increase of public trust, although continuous improvement is still required.          In conclusion, the transformation of narcotics evidence supervision at the Banjarbaru Police Resort is a strategic step in realizing accountability and public trust. The success of this transformation is highly influenced by the consistency in implementing SOPs, the utilization of information technology, and the enhancement of human resource capacity. Therefore, continuous efforts are needed in strengthening digital systems, improving facilities and infrastructure, and providing more intensive training and supervision to ensure that narcotics evidence management is carried out in a professional, transparent, and accountable manner.